Roles of Phase Separation for Cellular Redox Maintenance - Saito, Yuichi; Kimura, Wataru (Frontiers in Genetics, 2021)
The oxidation reaction greatly alters characteristics of various cellular components. In exchange for efficient energy production, mitochondrial aerobic respiration substantially increases the risk of excess oxidation of cellular biomolecules such as lipids, proteins, nucleic acids, and numerous small molecules. To maintain a physiologically balanced cellular reduction-oxidation (redox) state, cells utilize a variety of molecular machineries including cellular antioxidants and protein degradation complexes such as the ubiquitin-proteasome system or autophagy. In the past decade, biomolecular liquid-liquid phase separation (LLPS) has emerged as a subject of great interest in the biomedical field, as it plays versatile roles in the maintenance of cellular homeostasis. With regard to redox homeostasis, LLPS arose as a major player in both well-characterized and newly emerging redox pathways. LLPS is involved in direct redox imbalance sensing, signal transduction, and transcriptional regulation. Also, LLPS is at play when cells resist redox imbalance through metabolic switching, translational remodeling, activating the DNA damage response, and segregation of vulnerable lipids and proteins. On the other hand, chronic accumulation of phase-separated molecular condensates such as lipid droplets and amyloid causes neurotoxic outcomes. In this review we enumerate recent progress on understanding how cells utilize LLPS to deal with oxidative stress, especially related to cell survival or pathogenesis, and we discuss future research directions for understanding biological phase separation in cellular redox regulation.